Roots of the Western Self: Dualist and Monist Philosophies of Personal Identity (Global Journal of Human-Social Science, 2023)
Personal identity has rec ently appeared in the agenda of social sciences and humanities in a variety of ways There is a huge and expanding body of literature on identity and identity studies has gained significant importance in the social sciences and humanities across the globe This article aims to trace back the history of theories on Western personal identity from an interdisciplinary angle Defining identity raises many questions and invites different disciplines ranging from hermeneutics philosophy sociology psychology psychoanalysis linguistics anthropology and many more Answering questions about the nature of the self and the relationship between a person and her body led this article to trace back two lines of thought a dualist view that sees identity in terms of soul and body dichotomy and a monist view that focuses on the body as a defining element of identity The enormous philosophical interest in the idea of personal identity is due to concerns with the nature of personal identity throughout time and the relationship if any between personal identity and bodily identity
Keywords: identity-identity forma tion- soul-spirit- mindbody- dualist view-monist view- idealist-physicalist